Apao•AAO Joint Congress, Bali 2009 May 16 -19, 2009 - Satriah, Ismail
To report our experience in a patient with severe vernal shield ulcer treated with a combination of surgical debridement of the ulcer, supratarsal injection of triamcinolone acetonide, topical cyclosporine 0.05% and ketotifen fumerate 0.025%. Method: A patient with severe, resistant shield ulcer who did not res-pond to medical treatment with topical steroids, mast cell stabilizers and antihistamines was treated with surgical debridement of the ulcer, supratarsal injection of tria111Cinolone acetonide, topical cyclosporine 0.05% and ketetifen fumarate 0.025%. Results: The ulcer healed. well after three weeks. Topical cyclosporine was discontinued after two months. The patient was symptom free with no recurrence for six months. Conclusion: Combination of surgical debridemenr· of the ulcer, supratarsal injection of triamc!nolone acetonide, topical cyclosporine 0.05% and ketotifen fumerate 0.025% are effective as the treatment option in managing patient with severe vernal shield ulcer. Chronic use of topical steroid can be avoided.